Association between eating patterns and body mass index in a sample of children and adolescents in Northeastern Brazil - Nadya Helena Alves dos Santos; Rosemeire Leovigildo Fiaccone; Maurício Lima Barreto; Luce Alves da Silva; Rita de Cássia Ribeiro Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to assess the relationship between eating patterns and body mass index (BMI) in children and adolescents. This is a cross-sectional study of 1,247 male and female students, aged between 6 and 12, from public elementary schools in São Francisco do Conde, Bahia State, Brasil. BMI was used to analyze the children's nutritional status. Food consumption frequencies, in addition to demographic and socioeconomic information, were collected for each participant. Dietary patterns were identified through a factor analysis. The prevalence of overweight and obesity was 17.3% (10.2% overweight and 7.1% obese). Two eating patterns, "obesogenic" and "prudent", were identified. The former is characterized by sweets and sugars, typical Brazilian dishes, pastries, fast food, oils, milk, cereals, cakes, and sauces, and was positively associated with increased BMI (ßi = 0.244; p = 0.018). An "obesogenic" dietary pattern was associated with increased BMI.